The Russian Journey of Karel Havlíček Borovský - Heim, Michael Henry (Slavistische Beitraege, 1979)
Little is known of Karel Havlíček Borovský (1821-56) outside Czechoslovakia, but his fellow Czechs revere him. He is one of their nineteenth-century culture heroes - satirist of great finesse and a shrewd but always humane journalist and politician. The Russian journey proved to be the turning point in Havlíček's life.